2014
DOI: 10.1128/jvi.01067-14
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Infectivity and Virulence following Ocular-Only Aerosol Inoculation of Ferrets

Abstract: Respiratory pathogens have traditionally been studied by examining the exposure and infection of respiratory tract tissues. However, these studies typically overlook the role of ocular surfaces, which represent both a potential site of virus replication and a portal of entry for the establishment of a respiratory infection. To model transocular virus entry in a mammalian species, we established a novel inoculation method that delivers an aerosol inoculum exclusively to the ferret ocular surface. Using influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…4) (18), the sporadic and low-level detection of virus in NW samples from ferrets placed in direct contact with ferrets shedding virus to the environment suggests that ferrets in contact with infected ferrets were exposed to infectious virus but that the dose of NY/108 virus required for infection may be higher than what is typical for highly transmissible viruses in ferrets. The FID 50 of human and avian influenza viruses can be Ͻ10 infectious particles by intranasal or aerosol inoculation (19,23); ocular-only aerosol exposure of ferrets to Ͻ10 infectious particles of human and avian influenza viruses can result in robust infection (21). As such, our finding that ferrets exposed by the AR and concurrent ocular-aerosol inhalation routes to doses of 10 2.9 to 10 3.5 EID 50 of NY/108 virus did not become uniformly infected supports the suggestion that this virus has a higher threshold of infectivity and offers a possible explanation for why transmissibility in the ferret model was not observed, even though LPAI H7N2 viruses display a high capacity for transmission between shelter cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) (18), the sporadic and low-level detection of virus in NW samples from ferrets placed in direct contact with ferrets shedding virus to the environment suggests that ferrets in contact with infected ferrets were exposed to infectious virus but that the dose of NY/108 virus required for infection may be higher than what is typical for highly transmissible viruses in ferrets. The FID 50 of human and avian influenza viruses can be Ͻ10 infectious particles by intranasal or aerosol inoculation (19,23); ocular-only aerosol exposure of ferrets to Ͻ10 infectious particles of human and avian influenza viruses can result in robust infection (21). As such, our finding that ferrets exposed by the AR and concurrent ocular-aerosol inhalation routes to doses of 10 2.9 to 10 3.5 EID 50 of NY/108 virus did not become uniformly infected supports the suggestion that this virus has a higher threshold of infectivity and offers a possible explanation for why transmissibility in the ferret model was not observed, even though LPAI H7N2 viruses display a high capacity for transmission between shelter cats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inhalation of virus-containing aerosols, our laboratory has shown previously that ferrets may become productively infected with influenza virus following an ocular-only aerosol exposure or concurrent ocular-aerosol inhalation exposure (21,22). This work has revealed that very low levels of exposure of the ocular surface to aerosols can result in a productive respiratory infection in mammals, with heightened replication occurring when mammals are infected with aerosolized virus via both the ocular and respiratory routes.…”
mentioning
confidence: 93%
“…Similarly, studies quantitating the 50% infectious dose of influenza viruses in the ferret (FID 50 ) have revealed that both avian and human influenza viruses are capable of high infectivity in this species, with doses under 10 PFU leading to productive ferret infection following inhalation of virus-containing aerosols (24,36). Low-dose infection has also been documented following inoculation of ferrets by the ocular route (28).…”
Section: Inoculation Dosementioning
confidence: 99%
“…2, there are a wide array of established inoculation methods in the ferret, which include (but are not limited to) the intranasal, tracheal, ocular, and gastric routes, all of which can modulate where virus is deposited, replicates, and spreads throughout the course of infection. Further variability may be present within each of these routes; for example, ocular inoculation of ferrets may be conducted with either a liquid suspension or via aerosol exposure, and gastric inoculation may be conducted via the use of an endoscope or by ingestion (26)(27)(28). Thus, care should be taken to choose the inoculation route which best emulates and reflects the parameter examined in the study.…”
Section: Inoculation Routementioning
confidence: 99%
See 1 more Smart Citation